Implementación del algoritmo Threefish-256 en hardware reconfigurable - Nieto-Ramírez, Nathaly; Nieto-Londoño, Rubén Darío (Iteckne, 2014)
This article  presents  both  the  description and  results  of  the Threefish  cryptographic  algorithm hardware  implementation  for  encryption  process. The implementation of the algorithm was performed by using the iterative round architecture on the FPGA (Field Programmable Gate Array) Virtex-5 present in the development system XUPV5-LX110T. Place and route results show that the design Threefish-256 iterative round has a throughput of 551Mbps.